THE RELATIONS CHLOROPHYLL-A CONCENTRATION WITH CATCHED TUNA (Thunnus sp) IN WEST SUMATRA USING SATELLITE IMAGERY AQUA MODIS - Rosmasita '; Usman '; T. Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This purpose of this study to look at the spatial and temporal variations in the concentration of chlorophyll-a with aqua MODIS satellite image and look the relationship between the concentration of chlorophyll-a and catch of tuna (Thunnus sp) in West Sumatra by using correlation analysis. The location of fishing ground tuna (Thunnus sp) in West Sumatra at 00 0’ 0’’ S - 50 05’ 0’’ S dan 900 3’ 00’’E - 1020 37’ 00’’ E. The based coordinate of fishing ground and analyzed distribution of chlorophyll-a used satellite imagery of aqua MODIS in 2013, the catched of tuna held in distribution chlorophyll-a ranging 0,152 mg/m3 – 0,255 mg/m3. The catch is highest January (West season), April (Season West-East), July (East season) and October (Season East-West). The high catches of the highest of the season because effort high. Based on the value CPUE, in August categorized as good month with the arrest of most value CPUE 16.4142 kg /setting with catches of 22 670 kg (10%) of the total catch of 235 217 kg. The analysis showed height correlation between concentration of chlorophyll-a and tuna catches with coefficient correlation (r) and coefficient determination (R2) respectively 0,97 and 96,33%.Keyword : chlorophyll-a, Cacthed Tuna (Thunnus sp), aqua MODIS, correlation of coefficient (r) and coefficient of determination (R2).